Editorial for the Special Issue on Advances in Augmented and Mixed Reality in Education - Maria Meletiou-Mavrotheris; Konstantinos Katzis; Christos Dimopoulos; Ilona-Elefteryja Lasica (MDPI AG, 2023)
The Education Sciences Special Issue, Advances in Augmented and Mixed Reality in Education (Available online: https://www [...]